Implementation and application of functional languages 20th international symposium, IFL 2008, Hatfield, UK, September 10-12, 2008. revised selected papers - Scholz, Sven-Bodo; Chitil, Olaf (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 20th International Workshop on Implementation and Applications of Functional Languages, IFL 2008, held in Hatfield, UK, in September 2008. The 15 revised full papers presented were carefully reviewed and selected from 31 submissions. Topics of interest cover a wide range from novel language designs, theoretical underpinnings, compilation and optimisation techniques for diverse hardware architectures, to applications, programming techniques and novel tools.